On the identity of Pardosa consimilis Nosek, 1905 with a first description of the male and notes on two related species (Araneae: Lycosidae) - Naumova, Maria; Deltshev, Christo (Zootaxa, 2023)
More than a hundred years after its description in 1905, the wolf spider Pardosa consimilis Nosek, 1905 was known solely from the original description of a single female, the holotype. In the last decade there were reports of the species from Bulgaria. Several reports followed with possible records of the yet-unknown males but they were not described; these came from four countries at least: North Macedonia, Georgia, Albania and most recently from Iran. Pardosa consimilis belongs to the monticola group and can be assigned to separate albatula-complex. The aim of this article is to provide a description for the male of Pardosa consimilis for the first time and to redescribe the female, in comparison with its closest congeners P. albatula (Roewer, 1951) and P. blanda (C. L. Koch, 1833).